2005
DOI: 10.1158/1055-9965.epi-05-0160
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Mammographic Density with Dietary Factors in Japanese Women

Abstract: Background: A high percentage of mammographic dense area has been strongly associated with a risk of beast cancer. The present cross-sectional study evaluated the relations of percent density with dietary factors, such as fats, protein, dietary fiber, and soy isoflavones. Methods: Study subjects were 601 (348 premenopausal and 253 postmenopausal) Japanese women who were recruited from a mammographic screening center. The size of the total breast area and the dense area were measured quantitatively using an aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 21 publications
5
49
0
Order By: Relevance
“…This previous analysis, however, used a subjective estimate of percent density determined by an experienced radiologist. Other breast density studies have reported no associations for fruits (24), nuts and seeds (25), or cereals (24,25), and mixed findings regarding intake of vegetables (24,26), fish (24,26), dairy (24,27), and monounsaturated fatty acids or olive oil (27)(28)(29)(30) A Mediterranean diet effect may be more pronounced when quantified as an overall dietary pattern than when examined in terms of its specific components. Among current smokers in our sample, only three of the nine MDS components were statistically significantly associated with breast density, while six of the nine components were associated in the expected direction.…”
Section: Discussionmentioning
confidence: 96%
“…This previous analysis, however, used a subjective estimate of percent density determined by an experienced radiologist. Other breast density studies have reported no associations for fruits (24), nuts and seeds (25), or cereals (24,25), and mixed findings regarding intake of vegetables (24,26), fish (24,26), dairy (24,27), and monounsaturated fatty acids or olive oil (27)(28)(29)(30) A Mediterranean diet effect may be more pronounced when quantified as an overall dietary pattern than when examined in terms of its specific components. Among current smokers in our sample, only three of the nine MDS components were statistically significantly associated with breast density, while six of the nine components were associated in the expected direction.…”
Section: Discussionmentioning
confidence: 96%
“…For example, when SFAs has been replaced with polyunsaturated fat, a reduction in low-density lipoprotein cholesterol and a reduction in coronary heart disease risk have been observed (Woodside et al, 2008); and postmenopausal women with an intake of SFAs 415% of total energy intake presented a 7% higher mammary density than postmenopausal women consuming o15% of SFAs of total energy intake (Nagata et al, 2005). The mechanism is not clear, but according with these studies, and in the same way, an excess in SFAs intake could also be linked to asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Another [33] reported an inverse association between vegetable intake and breast density, but two others did not [32,34]. In nutrient-based analyses, several studies reported positive associations for total and saturated fat, protein, and alcohol intake [32,33,[35][36][37][38], and inverse associations for intake of fiber, carotenoids, calcium, and vitamin D [33,35,[39][40][41][42]. The generally inconsistent evidence for an association between diet and mammographic density in previous studies leaves open the possibility that mammographic density may not mediate dietary effects, if any, on breast cancer.…”
Section: Discussionmentioning
confidence: 99%